Transboundary conflicts and water governance in the Paraguay River Basin – South America (Sustainability in Debate, 2024)
This article analyses the conflicts and the structure of water governance in the Paraguay River Basin– South America – based on a review of documentary sources, specialised literature, and interviewswith key stakeholders operating in the basin. The study shows that the internal asymmetry of Braziland between this country and Paraguay is crucial in the definition of water use in the Basin, thusresulting in conflicts. The results of the study highlight the need for advances in the implementation ofagreements for the basin and the fact that these should include instruments that encompass new scalesof management and cooperation opportunities from local stakeholders, who have been neglected indecisions despite the coexistence of informal agreements between the parts.